2017 European Conference on Optical Communication (ECOC) 2017
DOI: 10.1109/ecoc.2017.8345893
|View full text |Cite
|
Sign up to set email alerts
|

Few Mode Ring-Core Fibre Amplifier for Low Differential Modal Gain

Abstract: We report a few-mode ring-core fibre amplifier for mode division multiplexed transmission. We achieve very low differential modal gain (<1dB) for 5 spatial modes over the C-band highlighting the benefits of the ring core approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Y. Jung et al demonstrated an OAM amplifier with topological charge | |=1 for the first time by utilizing an air-core EDF with a cladding-pumped configuration, in which up to 15.7-dB gain was achieved within the wavelength range of 1545-1600nm [75]. They later also reported a EDFA base on a GI-RCF [76], achieving < 1-dB DMG for five LP modes belonging to three MGs, which is the lowest DMG experimentally measured from any few-mode EDFA so far. The pumping configuration (core or cladding pumping), erbium doping distribution, and the RI profiles all have an impact on the overlap integrals between signal mode profiles and the erbium dopant distribution and thus the DMG performance.…”
Section: A Rcf-based Erbium Doped Fibre Amplifiers (Edfas)mentioning
confidence: 99%
See 1 more Smart Citation
“…Y. Jung et al demonstrated an OAM amplifier with topological charge | |=1 for the first time by utilizing an air-core EDF with a cladding-pumped configuration, in which up to 15.7-dB gain was achieved within the wavelength range of 1545-1600nm [75]. They later also reported a EDFA base on a GI-RCF [76], achieving < 1-dB DMG for five LP modes belonging to three MGs, which is the lowest DMG experimentally measured from any few-mode EDFA so far. The pumping configuration (core or cladding pumping), erbium doping distribution, and the RI profiles all have an impact on the overlap integrals between signal mode profiles and the erbium dopant distribution and thus the DMG performance.…”
Section: A Rcf-based Erbium Doped Fibre Amplifiers (Edfas)mentioning
confidence: 99%
“…H. Ono et al analysed how the combinations of the inner and outer radius of the SI-RCF affected the DMG of their 2-LP-mode RCF-based EDFAs and reported that low DMG could be achieved by adopting the inner radius of about 2.5-4 μm and the outer radius near the LP21 cut-off values [81,82]. Based on simulation [77] and experimental [76] results, Y. Jung et al showed that lower DMG of the EDFA could be achieved by utilizing GI-RCF under core-pumped operation without severe micro-bending, compared with that of the SI-RCF EDFA with large differential RI between core and cladding [78].…”
Section: A Rcf-based Erbium Doped Fibre Amplifiers (Edfas)mentioning
confidence: 99%
“…Firstly, control the pump scheme [4][5] . Secondly, there is distributed doping of erbium ions, such as ring doping of stepped refractive index core [6][7][8][9] . According to the principles, ring-core refractive-index profile (RIP) is used to fabricate the few mode (LP01, LP11a, LP11b ) erbium-doped fiber.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of the FM-EDF with ring-core [5][6][7][8], multi-layer refractive index [9][10][11] or air-hole [12], both high gains and low DMG are obtained. In the fiber design, the forward fixed variable (FFV) method is mainly applied [7,11], that is, sequentially changin * g one certain parameter within a suitable interval, while the others remain unchanged.…”
Section: Introductionmentioning
confidence: 99%